Six English Cantatas after the Italian Manner - Galliard, John Ernest 1687-1749; Hughes, John 1677-1720; Congreve, William 1670-1729; Prior, Matthew 1664-1721 (London Walsh & Hare, 1716)
The English cantata would retain a place on recitals and benefit concerts throughout the eighteenth century, performed in venues as diverse as the parlors private homes, the stages of opera houses, and the pleasure gardens of Vauxhall, of Ranelagh, and Marylebone. Composers such as Galliard, Henry Carey, John Stanley, Thomas Ame, William Boyce, Thomas Linley Jr., and James Hook would continue to compose English cantatas until the decline of the genre around 1790. (Jennifer Cable, Composing after the Italian Manner: The English Cantata 1700-1710, University of Richmond, 2014)
I. "Venus! Thy Throne of Beauty" / text: Mr Hughes -- II. The Reconciliation / Texts: Mr Congreve -- III. Apollo and Daphne / Text: Mr Hughes -- IV. "Beneath a verdant Lawrels" / text: Mr Prior -- V. "While on your blooming Charms" / Text: Mr Hughes -- VI. "Young Strephon" / Text: Mr Hughes
Engraved title page
Set of six solo continuo cantatas for alto/mezzo, each existing of 2 recitatives and 2 arias
Apart from an early Ann Arbor Facsimile reprint from the 1970ies, there seems to be no digital example available as yet
Ex libris Henri Prunières (Plate)
Ex libris "John Bishop from his kind friend Joseph Warren, August 13th 1845" (manuscript, in pencil on title page)
Keywords: 18th Century (1701-1800); Cantata; English; United Kingdom